The problem of choosing an effective road stabilization method on built-up landslide areas - Przemysław Baran; Ryszard Murzyn; Aleksandra Meres (Acta Scientiarum Polonorum. Formatio Circumiectus)
The aim of the article was to present feasible and effective road stabilization method on built-up landslide areas. The study has involved a landslide area situated in a designated municipality of Nowy Sącz district, in the Małopolska region. In the studied area, in the lower part of the slope, a landslide has formed, through which a road is running, leading to residential and farm buildings located further up. Bearing in mind the economic aspect, whereas also looking for the most effective way to stabilize the road in the studied area, we have analysed a number of possible technical solutions, which included: a French drain, anchor micropiles with reinforced concrete top plate, and ground anchors. The stability coefficient of the stabilized landslide has been chosen as the indicator of the effectiveness of the applied technical solution, which should take the value of no less than 1.5 after landslide stabilization. Based on the calculations we have conducted, we can conclude that the French drain is not sufficient, and neither is using the anchor micropiles on their own. Only a combination of these two solutions, along with additional anchoring, provides an effective protection of the area.